Settlement of Debt and Credit Disputes through Acta Van Dading (Case Study of Decision Number 8/Pdt.G.S/2023/PN Pwr and Decision Number 10/Pdt.GS/2020/PN Plj) - Aizah R Pambudi; K Kuswardani (Universitas Muhammadiyah Surakarta, 2024)
Conflicts in society always exist, especially conflicts related to debts and receivables, which in civil law terms are called debts and receivables dispute. Disputes are not always resolved through court, but rather by agreement betweem the parties inovved. Analysis of debt dispute resolution through acta van dading based on decision Number 8/Pdt.G.S/2023/PN Pwr and Decision Number 10/Pdt.GS/2020/PN Plj is a simole lawsuit that ended in peace because of the good faith of the parties in resolving peace. In the reseach used by the author, a normative juridical approach is used which is based on legal norms. The research aims to explain the responsibiliteies and legal consequences of settlement debts through acta van dading. The research results in this study will explain that there is a legal analysis related to resolving debt sttlement problems through the acta van dading which explains the responsibilities and legal consequences if debt collection is resolved through the acta van dading. The legal force of the acta van dading has executorial power which is binding and has permanent legal force.